INVESTIGATING EFL LEARNERS’ MORALS TOWARD CHARACTER EDUCATION AT STKIP MUHAMMADIYAH ACEH BARAT DAYA - Rina Syafitri; Puan Tursina (Universitas Islam Negeri Banda Aceh, 2019)
Being smart and having good grades are the dreams of students in learning process. However, to achieve those goals they have to be aware that affective or character aspect is equally important as cognitive and psychomotor aspect in the learning process. Thus, this study aimed to reveal the learning process of EFL learners’ morals toward education character. The research method of this study was quantitative; the questionnaire was used to collect the data. A total number of 34 participants were selected from each semester of English education department (EED) at STKIP Muhammadiyah Aceh Barat Daya by using convenience sampling. The data were analyzed quantitatively by using percentage. The results revealed that (1) most of students had positive attitudes toward character education in the learning process and (2) the common positive responses implied by EED students toward character education were in terms of commitment, responsibility and discipline. In summary, most of the students had a good character toward the implementation of education character in the classroom while having courses. However, there were only a few of EED students who were still not able to imply a good attitude toward education character in the classroom. Therefore, it is recommended for lecturers to give more attention toward the implementation of students’ education character in the classroom and continuously create strategies to develop students’ good character so that they will have good moral and knowledge.